(untitled) (American Economist: Journal of Economics Finance and Global Policy, 2026)
This article presents a statistical analysis of the dynamics of the 17 Sustainable Development Goals (SDGs) established by the United Nations in the Republic of Uzbekistan for the period 2017–2024. The research is based on official statistical data and covers economic, social, and environmental indicators. The study examines trends, growth rates, and their impact on the country’s sustainable development strategy. The results assess the effectiveness of ongoing reforms and identify existing challenges in achieving sustainable development.